Study of Isomorphism Between Lattice Groups And Fuzzy Groups (Latakia University Journal -Basic Sciences Series, 2018)
The objective of this studying is the important answer on the following open question in [5]: Let G and G' be two fuzzy groups and L(G), L(G') be lattices for them, respectively, if   is satisfied then do  is satisfied ?.We have shown that this statement don’t true in the case general, and we suppose some certain conditions on the purposed groups to be  the statement holds. Moreover, some important theorems are proved.